2001
DOI: 10.1177/000992280104000901
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Neonatal Meningitis in Very-Low-Birth-Weight Infants

Abstract: We sought to describe the clinical presentation and consequences of meningitis among 64 very-low-birth-weight (VLBW <1.5 kg) infants who had 67 culture-proven episodes of meningitis over an 18-year period, 1977 through 1995. Demographic and neonatal descriptors of meningitis and later outcomes were retrospectively examined and neurodevelopmental outcomes of 39 of 45 (87%) meningitis survivors were compared to those of nonmeningitis survivors followed up to 20 months corrected age. Causes of meningitis included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 22 publications
1
27
2
2
Order By: Relevance
“…A similar percentage of infants with elevated CSF WBC count (52%, 9/17) was observed in another cohort of infants with definite Candida meningitis, 9 and an even lower percentage (20%, 2/10) was found in another series. 10 In a recent multi-center study, 5% (14/293) of candidemic infants had Candida meningitis. 1 In our study of infants receiving an LP, 9% (7/77) of candidemic infants had evidence of Candida meningitis.…”
Section: Discussionmentioning
confidence: 98%
“…A similar percentage of infants with elevated CSF WBC count (52%, 9/17) was observed in another cohort of infants with definite Candida meningitis, 9 and an even lower percentage (20%, 2/10) was found in another series. 10 In a recent multi-center study, 5% (14/293) of candidemic infants had Candida meningitis. 1 In our study of infants receiving an LP, 9% (7/77) of candidemic infants had evidence of Candida meningitis.…”
Section: Discussionmentioning
confidence: 98%
“…In a 10-year study of neonatal meningitis in the United Kingdom, moderate or severe disability was detected in 12% of those with birth weight of Ͼ2,500 g, 31% of those with birth weight of 1,500 to 2,499 g, and 44% of those with birth weight of Ͻ1,500 g (204). Similarly, another group found that 41% of 39 VLBW survivors of neonatal meningitis suffered major neurologic sequelae, compared with 11% of matched control infants (114).…”
Section: Mortality and Morbidity Associated With Bacterial Sepsismentioning
confidence: 95%
“…Diagnosis of meningitis is problematic in VLBW infants since the CSF white blood cell count is an unreliable indicator of meningitis in these infants and the lumbar puncture is often delayed until after antimicrobials have been administered, when the patient is judged to be more stable (114). There are no data in preterm infants examining trends in CSF pleocytosis after antibiotics have been administered.…”
Section: Definitions Of Sepsis and Focal Infections In Very-low-birthmentioning
confidence: 99%
“…E-mail: verakrebs@uol.com.br Low birth weight newborns present a 3-fold increased risk of acquiring meningitis when compared to those whose birth weight is ≥2500 g 1 . Among very low birth weight neonates (<1500 g) the risk is a 10 to 17-fold higher [2][3][4] . In addition to the immaturity of the immunological system, these neonates frequently present risk factors for infection related to maternal diseases or neonatal conditions 1,3,5 .…”
mentioning
confidence: 99%